Women’s Satisfaction with Hospital Based Intrapartum Care in a Medical College of Western Nepal - Bajracharya, Srishti; Gurung, Saraj; Shakya, Sandeep (Journal of Universal College of Medical Sciences, 2023)
INTRODUCTION Birth satisfaction is a multi-dimensional concept comprising structure, process and outcome of care that inﬂuence postnatal adjustment. Mother’s satisfaction during the birthing process is an important indicator in evaluating quality of maternity services. The aim of the study is to ﬁnd out the women’s satisfaction with hospital based intrapartum care in a medical college of western Nepal. MATERIAL AND METHODS Cross-sectional analytical study was conducted to ﬁnd women’s satisfaction with hospital based intrapartum care in a medical college of western Nepal among 332 postpartum inpatient women delivered in Lumbini Medical College and Teaching Hospital, Pravas, Palpa, who were selected by using purposive sampling technique. A pretested interview schedule was used for data collection. Descriptive statistics and inferential statistics were used for data analysis. RESULTS The study ﬁndings revealed that about half of the respondents (50.9%) were satisﬁed with hospital based intrapartum care. The level of satisfaction was signiﬁcantly associated with gravida (p=0.008), type of labor onset (p=0.007) and episiotomy status (p<0.001). CONCLUSION The study ﬁndings conclude that women attending teaching hospital for delivery tend to be somewhat satisﬁed with hospital based intra-partum care. Adequate counseling, reassurance and supportive care of women during intrapartum period might increase their satisfaction with intrapartum care.